Evisceration and other complications of abdominal drains. Issue 789 (July 1991) - Loh, A.; Jones, P. A.
Abstract : Drainage following major abdominal surgery remains controversial. A case of small bowel evisceration through a Wallis drain site after an abdomino-perineal excision of rectum is reported as a complication of abdominal drainage.